Enhancing mu-ERD through combined robotic assistance and motor imagery: a novel approach for upper limb rehabilitation - Yasuda, Hiroki; Ueda, Masaya; Ueno, Keita; Naito, Yasuo; Ishii, Ryouhei; Takebayashi, Takashi (Frontiers in Human Neuroscience, 2025)
IntroductionPrevious research has suggested that mu-event-related desynchronization (mu-ERD) reflects neural activity associated with motor observation and execution, primarily within the sensorimotor cortex. This study aimed to investigate the effects of combining robotic full-assist therapy with motor imagery on mu-ERD in healthy adults for potential application in stroke patients with severe upper limb paralysis.MethodsFifteen healthy adults were included in this study. Each participant performed three conditions using the ReoGo-J® robotic system: voluntary movement, full-assist robotic therapy without motor imagery, and full-assist robotic therapy with motor imagery. Electroencephalography (EEG) was used to measure mu-ERD, focusing on the 8–10 Hz and 10–13 Hz frequency bands at the C3, C4, Cz, and Pz electrodes.ResultsSignificant differences in mu-ERD occurrence were observed at C3 (8–10 Hz) and C4 (10–13 Hz) between the conditions. The combination of motor imagery and robotic therapy demonstrated a higher frequency of mu-ERD occurrence than the other conditions, with moderate effect sizes. However, no significant differences in mu-ERD attenuation rates were found between the conditions. This suggests variability in individual responses.DiscussionThese findings highlight the potential of robotic full-assist therapy combined with motor imagery to stimulate neural mechanisms associated with motor recovery. Future studies should include a larger sample size and patients with stroke to validate these findings and explore their clinical applications.